2007
DOI: 10.1177/0149206306297581
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Feedback Environment and Role Clarity Model of Job Performance

Abstract: Many researchers have demonstrated that proactive feedback seeking, the efforts made by employees to reduce uncertainty surrounding the acceptability of their performance, is both an important individual and organizational resource (Ashford, 1986; Ashford & Cummings, 1983). In particular, research has focused on what Ashford and Cummings (1983) termed inquiry, the active request for feedback. This form of feedback seeking has shown clear benefits for both the individual and the organization (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(197 citation statements)
references
References 60 publications
8
181
0
1
Order By: Relevance
“…A "role" is a set of expectations or norms applied to the incumbent by others in the organization; thus, employees with high role clarity possess a clearer understanding of their requirements (Whitaker et al 2007). Role clarity has been investigated in the context of employees' roles (Woodard et al 1994), consumers' roles (Meuter et al 2005), and channel members' roles (Teas and Sibley 1980).…”
Section: Hypothesis 3: Employees' (A) Feelings Toward and (B)mentioning
confidence: 99%
“…A "role" is a set of expectations or norms applied to the incumbent by others in the organization; thus, employees with high role clarity possess a clearer understanding of their requirements (Whitaker et al 2007). Role clarity has been investigated in the context of employees' roles (Woodard et al 1994), consumers' roles (Meuter et al 2005), and channel members' roles (Teas and Sibley 1980).…”
Section: Hypothesis 3: Employees' (A) Feelings Toward and (B)mentioning
confidence: 99%
“…Researchers agree that before feedback can be used it must be accepted and internalized (Ashford, 1986), and as result of its theoretical importance, feedback acceptance has received extensive empirical attention (e.g., Brett & Atwater, 2001;Ryan, Brutus, Greguras, & Hakel, 2000). Researchers has suggested that feedback environment may have important effects on employees" task performance and organizational citizenship behaviour (OCB) (e.g., Kluger & Denisi, 1996;Norris-Watts & Levy, 2004;Rosen, Levy, &Hall, 2006;Steelman et al, 2004;Whitaker, Dahling, & Levy, 2007).…”
Section: Job Characteristics and Job Performance Relationship At Facementioning
confidence: 99%
“…This proved to be a relatively difficult field of learning in both arenas examined, and there were also certain considerations of national character involved in people's understanding of the difficulties of giving and receiving feedback. When employees have greater access to information about behaviours that are acceptable and desired at work and the feedback environment is of high quality and supportive of feedback seeking, then, work role clarity, work outcomes and job satisfaction are enhanced (Rosen et al 2006;Whitaker et al 2007).…”
Section: Feedback and Learningmentioning
confidence: 99%